Trajectory tracking control for autonomous underwater vehicles under quantized state feedback and ocean disturbances. (15th July 2022) - Zhou, Bin; Su, Yumin; Huang, Bing; Wang, Weikai; Zhang, Enhua
Abstract: For the autonomous underwater vehicle (AUV) platform, state quantization is a widely existing phenomenon as the result of I/O signal conversion between hardware module and control module. This article considers such an adaptive trajectory tracking control problem for AUVs with the effects of quantized state feedback and ocean disturbances. To ensure the stability of the closed-looped system under quantized states and unmeasurable ocean disturbances, a novel quantized extended state observer (QESO) is firstly proposed. Then, an adaptive anti-disturbance control scheme is developed to achieve the trajectory tracking control goal. The main advantage of the proposed algorithm paper lies in that the resulted controller is established without any usage of continuous states. Besides, rigorous stability analysis validates the uniformly ultimately boundedness of the resulting closed-loop system under quantized states. Simulation experiments demonstrate the effectiveness and robustness of the proposed algorithms. Highlights: The trajectory tracking control problem of AUVs is solved under the effects of states quantization. A novel quantized extended state observer is proposed to approximate the unknown disturbances. A backstepping controller is proposed to solved the quantized state feedback control problem.